Online Lodging Service in Industry - Permatasari, S; Hassanah, Hetty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out the marketing strategies of an online lodging service. This study used descriptive qualitative methods for several online-based lodging services. The results of this study are the development of information technology has played an important role in providing convenience for people, especially in the world of online business. The focus includes economic entrepreneurship, business, communication, and information technology. This online lodging service becomes a media that provides business opportunities for everyone who can improve the Indonesian economy.